Consider Mitochondrial DNA Rearrangements as a Cause of Idiopathic Pancreatitis - Finsterer, Josef; Mehri, Sounira (Turkish Journal of Gastroenterology, 2025)
Cite this article as: Finsterer J, Mehri S. Considermitochondrial DNA rearrangements as a cause of idiopathic pancreatitis. Turk J Gastroenterol. 2025;36(4):263-264.